Enhancement of catalytic performance of a metagenome-derived thermophilic oligosaccharide-specific xylanase by binding module removal and random mutagenesis - Boonyapakron, Katewadee; Chitnumsub, Penchit; Kanokratana, Pattanop; Champreda, Verawat (Journal of bioscience and bioengineering, 2021)
Xylo-oligosaccharide (XO) is a promising pre-biotic with applications in food, feed and healthcare products. XO can be produced by enzymatic digestion of xylan with xylanase. In this study, we aimed to improve the biochemical properties relevant to catalysis and kinetics of X11, a thermophilic glycosyl hydrolase (GH) family 11 endo-β-1,4-xylanase derived from a metagenomic library isolated from sugarcane bagasse, under high-temperature conditions preferred for XO synthesis. Removal of a carbohydrate-binding module (X11C) resulted in 6.5 fold greater catalytic efficiency. X11C was further improved by a Pro71Thr mutation in the X11P variant obtained from a random mutagenesis library, which exhibited 15.9 fold greater catalytic efficiency compared with wild-type X11 under the enzyme's optimal conditions of 80°C and pH 6.0. Homology modeling suggested that the improved performance of X11P could be attributed to formation of an extra H-bond between Thr71 and Ser75, which stabilizes the key catalytic residue Glu180 at the active pocket and β-sheet layers and agrees with the respective increase in melting temperature (Tm) where X11P >X11C >X11 as determined by differential scanning fluorimetry. The X11P variant was tested for hydrolysis of beechwood xylan, which showed X6 as the major product followed by X3 and X4 XOs. The highest yield of 5.5 g total XOs product/mg enzyme was observed for X11P, equivalent to 3.7 fold higher than that of wild-type with XO production of >800 mg/g xylan. The X11P enzyme could be developed as a thermophilic biocatalyst for XO synthesis in biorefineries. [Display omitted] •XO-specific X11P was obtained by CBM removal and directed evolution.•X11P worked optimally at 80°C with 4.1x increase in specific activity.•X11P exhibited lower Km (4.6x) and higher kcat/Km (15.9x) compared to X11.•A 3.1 folds increase in XO yield (X6 > X3 > X4) was achieved by X11P.•Introduced H-bond (Thr71-Ser75) stabilized catalytic residue Glu180.